PENGARUH ANALISIS KINERJA DAN PEMETAAN KOMPETENSI PEGAWAI TERHADAP KEBUTUHAN PELATIHAN (STUDI TERHADAP PEGAWAI TINGKAT MANAJER DAN SUPERVISOR DI KANTOR PT PLN (PERSERO) DISTRIBUSI JAWA BARAT DAN BANTEN - Sendianto Sendianto (Sekolah Tinggi Manajemen IMMI Jakarta, 2019)
The purpose of this study was to measure the effect of performance analysis and mapping of employee competencies on the training needs of managerial and supervisory level employees in the offices of PT PLN (Persero) Distribution of West Java and Banten. The research method used was explanatory and verificative explanation, with 79 respondents, and data analysis used path analysis to determine the influence between the variables. The results of the path analysis test partially show that there is a positive and significant influence from: (1) Performance analysis of the training needs of 90.25%; (2) mapping employee competencies to training needs by 0.25%; (3) Simultaneously performance analysis and mapping of employee competencies influence training needs of 98.01%. Suggestions, measurement tools for performance appraisal are continuously improved, soft competency of continuous learning and relationship building is improved through soft skills training, and job analysis through job description and job specifications needs to be reviewed.